Pengaruh Motivasi Belajar Mahasiswa PAI UNP melalui Pergaulan - Naputra, Danil; Sulaiman, Sulaiman (Lembaga Yasin AlSys, 2024)
Sociability is a continuation of the process of social interaction that exists between individuals and their social environment, then motivation is one of the things that affects the success of learning activities, without the learning process will not run well. This study aims to determine the effect of association on the learning motivation of PAI students class of 2020 UNP. This research includes quantitative research with the type of correlation and descriptive statistical analysis techniques. The data collection method uses primary data. In this study using validity test and reliability test. There were 60 PAI 2020 UNP students who were sampled in this study. Data data were collected through instrument questionnaires from socialization and learning motivation variables. The results of the data data are processed through statistical calculations and average correlations obtained through the use of SPSS 16.0. The data shows that there is a positive and significant influence between socialization on learning motivation by 59.3%. The results showed that association partially had a positive and significant effect on learning motivation, which means that learning motivation is influenced by association. Researchers recommend that be smart in choosing associations.